Closing the cycle? Potential and limitations of Water and Sanitation Safety Plans (WSSP) for Latin American metropolitan areas - Clavijo Lara, Araceli Maria (2020)
Water and sanitation management faces major challenges due to the rapid urban growth of metropolitan areas and the resulting pressure on water resources. Metropolitan areas often combine formal and informal water and sanitation services and regularly face shortages, leakages, and other situations involving risk to users and the environment. This work presents an integrated approach for the development and implementation of a Water and Sanitation Safety Plan (WSSP) for metropolitan areas, especially in developing countries. The plan allows for the assessment of all the risks associated with the components of the urban water cycle by means of a semi-quantitative approach. In the case study described, the overall risk estimated was 37.2% (44.0 and 30.3% for the drinking water supply and sanitation sub-systems, respectively). Highest risk values were obtained for components of water treatment (53.0%) and wastewater treatment (51.7%). Our assessment took into account both formal and informal sanitation components of the water and wastewater management cycle and included a multi-institutional analysis of the entire system. Results obtained may contribute to establishing new policies and guidelines for the protection of public health and the local environment in our case study and other areas of the region with similar contexts and comparable institutional settings.